Sustainable development and quality of life in Lithuania compared to other countries - Štreimikienė, Dalia; Barakauskaitė-Jakubauskienė, Neringa (Technological and Economic Development of Economy, 2012)
The paper presents the definition of quality of life and its relationship with sustainable development. The paper analyses and compares the indicators of quality of life in Lithuania with other countries. A quality of life is an explicit or implicit policy goal. Various measurements and indicators to evaluate a quality of life were proposed during the recent years however there are no widely accepted objective indicators of quality of life able to compare countries. Sustainable development concept proposes new approach to measure quality of life. Therefore the aim of sustainable development is to increase quality of life. Quality of life can be addressed in terms of people health, the state of economy, employment, infrastructure development, crime and environment. All these indicators are interrelated as economic development creates preconditions to maintain public health, develop social and technical infrastructure, to increase employment, to ensure quality of environment, to tackle with crime etc. From the other point of view healthy and satisfied with the quality of life nation have positive impact on stable economic growth.